Efektivitas Pelayanan Korban Kekerasan Terhadap Perempuan Dan Anak Melalui Program Bunga Tanjung Di RSUD Tarakan Jakarta - Purba, Abigail Putri Anggita (Universitas Muhammadiyah Mataram, 2022)
The high number of violence against women and children makes the government seek to form policies and public services to support security for women and children. In this case, Tarakan Hospital as a public service unit in the health sector formed the Bunga Tanjung program innovation as an Integrated Service Center iin serving victims of violence against women and children in collaboration with P2TP2A and the Police in providing comprehensive services from medical, psychosocial, and social services. legal counselling. The Bunga Tanjung program has successfully entered the TOP 45 Public Service Innovations in 2020 organized by the Ministry of Administrative Reform and Bureaucratic Reform as well as representing Indonesia in the 2021 United Nation Public Service Awards (UNPSA) Competition. This study aims to determine the effectiveness of the Bunga Tanjung program in provide comprehensive services to victims of violence. The method used in this research is a qualitative method. The results showed that the Bunga Tanjung program has been running effectively based on 3 indicators of program effectiveness according to Duncan namely goal achievement, integration, and adaptation